Understanding The Internalization Stratey For MSMEs - Ita Prihatining Wilujeng (International Journal of Science, Technology & Management, 2021)
Recently many micro, small, and medium enterprises (MSMEs) play important role in international market. They are expanding their business to international market. Internationalization provides many strategic benefits to the business of MSMEs. However, for many business groups on this scale, internationalization is not easy due to limited resources and capabilities. In order to achieve efficient and effective internationalization, it is important to understand the determinants of MSMEs internationalization and its relationship to the internationalization of firms. This study explores how the international orientation of employer, human resources, technology capabilities of the company, and the external environment can explain understanding the level of internationalization of MSMEs. The study showed that the orientation of entrepreneurial and investment in human resources is an important factor to explain the internationalization MSMEs. Additionally, technology turbulence and market similarities moderate this relationship. The results imply that the manager/owner of MSMEs should consider these internal and external factors in order to improve their performance in the international market.